2020
DOI: 10.3390/life10040046
|View full text |Cite
|
Sign up to set email alerts
|

Association between Occupational Noise and Vibration Exposure and Insomnia among Workers in Korea

Abstract: Background: The effect of noise and vibration exposure on disturbed sleep has been investigated in the past. However, this study was carried out to investigate the relationship between workplace noise and vibration exposure with insomnia amongst representative Korean workers, both simultaneously and separately. Methods: Our research analyzed an overall population of 30,837 workers aged 15 years or older using data derived from the 5th Korean Working Conditions Survey (KWCS) conducted in 2017. Chi-squared tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Insomnia is another ailment reported by workers. Nari found in his study an increased risk of developing this discomfort in both genders, especially if exposed to vibrations at the same time (1.83/ CI 1.61-2.07 in men and 3.14/ CI 2.76-3.57 in women) [45]. Sleep disturbances appear to be triggered by annoyance, which in turn is related to noise exposure but they does not appear to be related to the age of workers [46].…”
Section: Main Disordersmentioning
confidence: 88%
“…Insomnia is another ailment reported by workers. Nari found in his study an increased risk of developing this discomfort in both genders, especially if exposed to vibrations at the same time (1.83/ CI 1.61-2.07 in men and 3.14/ CI 2.76-3.57 in women) [45]. Sleep disturbances appear to be triggered by annoyance, which in turn is related to noise exposure but they does not appear to be related to the age of workers [46].…”
Section: Main Disordersmentioning
confidence: 88%
“…This is in line with the results of the current study. According to many prior studies, the synergistic effect of noise and vibration has been shown to impact on health outcomes, such as cognitive performance, hearing loss, and headache/eyestrain [ 25 ]. In animal studies, conducted by Hamernik, and in an experimental study conducted by Huang and Griffin [ 26 ], a prediction model was created for 24 healthy young people in order to examine the level of discomfort caused by exposure to continuous, whole-body vibration and noise.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia is another ailment reported by workers. In his study, Nari found an increased risk of developing this discomfort in both genders, especially if exposed to vibrations at the same time (1.83/ CI 1.61-2.07 in men and 3.14/ CI 2.76-3.57 in women) [51]. Sleep disturbances appear to be triggered by annoyance, which in turn is related to noise exposure, but they do not appear to be related to the age of workers [52].…”
Section: Main Disordersmentioning
confidence: 91%